Ultra-rapid cooling of ibex sperm by spheres method does not induce a vitreous extracellular state and increases the membrane damages - Bóveda, Paula (2020)
Sperm cryopreservation by ultra-rapid cooling based on dropping small volumes of sperm suspension directly into liquid nitrogen, has been successful in some wild ruminant species, including the Iberian ibex (Capra pyrenaica). In ultra-rapid cooling, the contents of these droplets are expected to enter a stable, glass-like state, but to the best of our knowledge no information exists regarding the presence or absence of ice formation in the extracellular milieu when using this technique. Different modifications to the extracellular milieu likely inflict different types of damage on the plasmalemma, the acrosome and mitochondrial membranes. The aims of the present work were: 1) to examine the physical state of the extracellular milieu after cryopreservation at slow and ultra-rapid cooling rates—and thus determine whether ultra-rapid cooling vitrifies the extracellular milieu; and 2) to compare, using conventional sperm analysis techniques and scanning and transmission electron microscopy, the damage to sperm caused by these two methods. Sperm samples were obtained by the transrectal ultrasound-guided massage method (TUMASG) from anesthetized Iberian ibexes, and cryopreserved using slow and ultra-rapid cooling techniques. Sperm motility (22.95 ± 3.22% vs 4.42 ± 0.86%), viability (25.64 ± 3.71% vs 12.8 ± 2.50%), acrosome integrity (41.45± 3.73% vs 27.00 ± 1.84%) and mitochondrial membrane integrity (16.52 ± 3.75% vs 4.00 ± 0.65%) were better after slow cooling (P<0.001) than after ultrarapid technique. Cryo-scanning electron microscopy (Cryo-SEM) suggested that the vitrified state was not achieved by ultra-rapid cooling, and that the ice crystals formed were smaller and had more stretchmarks (P<0.001) than after slow cooling. Scanning electron microscopy revealed no differences in the types of damage caused by the examined techniques, although transmission electron microscopy showed the damage to the plasmalemma and mitochondrial membrane to be worse after ultra-rapid cooling. In conclusion ultra-rapid cooling provoked more membrane damage than slow cooling, perhaps due to the extracellular ice crystals formed.